Suction measurements using fiber optic sensors - Tay, Benjamin Chia Meng (2008)
Soil suction is important in explaining the behaviour of unsaturated soils. Unsaturated soil refers to soils with solid, liquid and gaseous phases in it (i.e. soil particles, soil water and air), and these kind of soils are the most commonly encountered in the field. Knowing the suction of a particular soil would allow the shear strength, volume change and hydraulic behaviour of the soil to be characterised. Having instrumentation that is simple to use and effective in the field that can measure the various suction components of soil would be ideal, but unfortunately this is not presently the case. Soil is not a man-made material; the difficulties involved in measuring soil parameters are well known as soil does not behave in a linear fashion. Experiments done in the laboratory often do not match the soil conditions on the site where the soil was sampled. It is important to know the suction of soil as the knowledge will, for example, enable safety standards to be improved on construction sites, or improve crop yield by providing perfect soil conditions for agriculture.